Automated Real Time In-Store Retail Marketing Using Beacon - Kothari, Jigar; Shah, Trupti; Nagaria, Bhavin; Choubey, Apurv; Pabba, SaiDeepthi (International Journal of Computer Sciences and Engineering, 2025)
Bluetooth Special Interest group designed the version 4.0+ of the Bluetooth device termed as Bluetooth Low Energy (BLE). It is a wireless personal area network technology. Bluetooth Low Energy (BLE) is a newly emerged technology targeting low-power, low-cost wireless communications within medium or short range. BLE has extended the already wide acceptance of Bluetooth and is an ideal choice for a variety of sensor-based products, as well as ubiquitous mobile devices [1]. This group aimed at novel applications in fitness, security, healthcare and home entertainment industries. Bluetooth Low Energy (BLE) is also called as Bluetooth Smart device. This device is application friendly.lt is built for the Internet of Things (IoT). BLE is the version 4.0+ of the Bluetooth specification.